2014
DOI: 10.1080/10437797.2014.947163
|View full text |Cite
|
Sign up to set email alerts
|

The Implicit Curriculum in an Urban University Setting: Pathways to Students’ Empowerment

Abstract: Professional schools are developing conceptual frameworks that can be used to assess and improve implicit curricula. Students' professional empowerment, defined to include perceived professional competence and identity, may be considered a vital outcome of these efforts. Our study evaluated measures and tested a path model that included perceptions of characteristics of implicit curricula (i.e., faculty and staff diversity, supportive faculty, opportunity role structure, and access to infor mation) and mediati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Studies examining PE at the intrapersonal level , through the SPCS, have found that persons reporting greater control over key aspects in their life and are involved in leadership activities have a greater neighborhood SOC (Zimmerman & Zahniser, ), stronger beliefs of community control (Peterson et al., ; Peterson, Farmer, & Zippay, ), and are more involved in organizational and community activities (Christens & Lin, ; Christens & Speer, ). For instance, Zimmerman, Ramirez‐Valles, and Maton () found that PE, over time, assisted, and even protected, Black urban youth from the negative consequences of helplessness on mental health indicators; meaning, PE is likely to buffer urban youth from negative mental health symptoms and other associated consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining PE at the intrapersonal level , through the SPCS, have found that persons reporting greater control over key aspects in their life and are involved in leadership activities have a greater neighborhood SOC (Zimmerman & Zahniser, ), stronger beliefs of community control (Peterson et al., ; Peterson, Farmer, & Zippay, ), and are more involved in organizational and community activities (Christens & Lin, ; Christens & Speer, ). For instance, Zimmerman, Ramirez‐Valles, and Maton () found that PE, over time, assisted, and even protected, Black urban youth from the negative consequences of helplessness on mental health indicators; meaning, PE is likely to buffer urban youth from negative mental health symptoms and other associated consequences.…”
Section: Introductionmentioning
confidence: 99%
“…While Black male social work students can benefit from meaningful relationships with Black social work professors, these relationships are less probable, given that only 16% of full and part-time faculty in U.S. accredited social work programs are Black (Council on Social Work Education [CSWE], 2016). For accredited programs lacking ample representation of full-time Black faculty, a purposeful (re)assessment of their implicit curriculum could warrant practices that aggressively recruit and retain these faculty (Peterson, Farmer, & Zippay, 2014).…”
Section: Meaningful Relationships With Black Facultymentioning
confidence: 99%
“…Further, building trust and a relationship contributes to members' empowerment and leads to achieving goals beyond expectation (Forenza and Mendonca, 2017;Janssen et al, 2015). Underpopulated settings Opportunity role structure (Alcantara, 2012;Forenza, 2014Forenza, , 2016Forenza and Mendonca, 2017;Peterson et al, 2013;Maton, 2008;Powell, 2013;Powell and Peterson, 2014;Segal et al, 2013;Tesdahl and Speer, 2015) Collaboration between coempowered subgroups (Carrasco et al, 2016) Resolved ideological conflict Resource identification Leadership (Forenza, 2014(Forenza, , 2016(Forenza, , 2017Forenza and Mendonca, 2017;Janssen et al, 2015;Maton, 2008;Powell and Peterson, 2014;Valsania et al, 2016) Social support (Christens and Lin;2014;Forenza, 2016Forenza, , 2017Forenza and Mendonca, 2017;Powell, 2013;Powell and Peterson, 2014) Group-based belief system (Forenza, 2014(Forenza, , 2017Maton, 2008;Powell, 2013;Powell and Peterson, 2014) New processes and outcomes of intraorganizational empowerment Team empowerment (Yiannakis et al, 2006) Sense of community (Christens and Lin, 2014;Hughey et al, 2008;…”
Section: Organizational Empowermentmentioning
confidence: 99%